Criminal Mediation and Customary Sanctions for Children in Conflict with The Law - Sartika Saimima, Ika Dewi; Haryani Putri, Anggreany; Romasindah Aidy, Widya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
Restorative justice is a method used to resolve child conflict cases, involving criminal mediation and customary sanctions. This model involves all parties involved, including victims, victim families, perpetrators, indigenous communities, and law enforcement. The study investigates the treatment of children involved in criminal acts, focusing on criminal mediation and customary sanctions. It uses a normative/doctrinal approach, examining child protection law, the child criminal justice system, and arbitration law. Examples of customary sanctions applied by Lampung, Minangkabau, and Bali tribes are also included. The research uses the IRAC method and library research to gather secondary data. The study aims to provide an overview of child case settlement mechanisms, incorporating vertical and horizontal synchronizations. However, inconsistencies in applying restorative justice, particularly in cases of children in conflict with the law, are highlighted. Customary sanctions should be used for children in conflict with the law, and criminal mediation is proposed as an alternative. Family and community conferences are also proposed as solutions.